Frequency and susceptibility pattern of uropathogenic Enterobacteriaceae isolated from patients in Algiers, Algeria - Abdelhakim Aouf; Taha Gueddi; Bilal Djeghout; Houria Ammari (Journal of Infection in Developing Countries)
Introduction: The frequency of Enterobacteriaceae involved in urinary tract infections (UTI) has increased significantly since the early 1990s, particularly in at-risk facilities such as resuscitation, surgery, urology and nephrology. The objective of this study was to evaluate the antimicrobial susceptibility of Enterobacteriaceae causing urinary tract infections (UTIs)at the University Hospital Centre of Benimessous in Algiers.